Communicative Taboo in Russian and Uzbek Languages - Chorievna, Jumaeva Shakhlo (European Journal of Life Safety and Stability (2660-9630), 2021)
A ban arising in the sphere of public life is usually called a taboo. Taboos have been known to people since antiquity and were originally associated with the beliefs of peoples. For example, the verbal designation of death, illness, the names of gods and some animals was prohibited. And to replace taboo words, other words were needed, which linguists call euphemisms. Why does the language need them? What are they? What is the impact on communication in general? In this article, the author attempts to say communicative taboos in the Russian and Uzbek languages.